Education in Latin America at the turn of the 20th century: ‘epistemologies of the South’ versus ‘education in complexity’ - Elena Anatolievna Zhizhko; Gali-Aleksandra Beltrán (Edukacja Ustawiczna Dorosłych)
In this work we present the results of a theoretical pedagogical research, which objective was to determine the theoretical, political and ideological trends that permeate the Latin American educational field from the end of the 20th century and until the beginning of the third decade of the 21st century, which provide the support for the development of new paradigms in regional education, in particular, to analyze the epistemologies of the South and education in complexities. Authors found, that from the end of the 20th century and until the beginning of the third decade of the 21st century, the education in Latin America is influenced by leftist theoretical, political and ideological tendencies, which advocate the development of the so-called epistemologies of the South, full of cultivation and protection of tradition. On the other hand, as its alternative, since the end of the 20th century, education in complexities has been taking shape with its vision of rationalized and secular social life, creating new paradigms in regional education.